'Down the Back Paddock': a programme to educate local primary school children about safety on rural properties. (7th October 2012) - Kerry, Miles
Abstract : Background: With 38% of the Waimakariri District population living rurally on farms or lifestyle blocks, rural safety is key area of focus for Injury Prevention Waimakariri. Furthermore, since the earthquakes more Christchurch people are moving to the Waimakariri District. Therefore, the need for rural safety education is now greater than ever. Not only rural children, but also those living in urban areas who regularly visit rural properties are being injured through unsafe practices being employed or through lack of knowledge about rural dangers. Aim: 'Down the Back Paddock' is a rural education programme aimed at increasing children and teachers' awareness of the risks associated with a rural environment. The purpose is to better educate children and, through them, adults to help create a better safety culture on farms and lifestyle blocks in the future. Method: 'Down the Back Paddock' is run in schools with experts delivering messages on a variety of safety-related topics specific to rural contexts. The programme has been developed by a local school principal and also designed to fit the New Zealand Curriculum Framework objectives. Schools are visited on a 4-yearly basis to reinforce the message; with each child receiving the message twice during their primary school years. Now in its eighth year of operation 'Down the Back Paddock' has been run in all the rural primary schools at least twice and now includes many urban schools. Result/Outcome: Evaluations from teachers, tutors and the children, plus feedback from parents point to the programme's success. Word of this success and we are receiving enquires from other Local Authorities and organisations inquiring about running it in their area.